Differences in Spinopelvic Kinematics in Sweep and Scull Ergometer Rowing - Strahan, A.; Burnett, A.; Caneiro, Joao; Doyle, M.; O'Sullivan, Peter; Goodman, C. (Lippincott Wiliams and Wilkins, 2011)
Objective: The spinopelvic kinematics of sweep and scull have yet to be investigated, despite evidence suggesting that sweep rowing may be provocative for low back pain (LBP). The aim of this study was to determine whether differences existed in spinopelvic kinematics in high-level rowers without LBP in sweep and scull ergometer rowing. Design: Repeated measures study. Setting: Institute of Sport Laboratory. Participants: Ten high-level rowers. Interventions: Kinematics of the pelvis, lower lumbar, upper lumbar, and lower thoracic regions during the drive phase of the rowing stroke were measured while rowing on an interchangeable sweep/scull ergometer. Main Outcome Measures: Total and segmental spinopelvic kinematics. Results: Sweep rowing showed greater lateral bend (P < 0.05) throughout the stroke, which was predominately due to movement of the upper lumbar and lower thoracic regions. Furthermore, sweep rowing displayed a greater magnitude (P < 0.05) of axial rotation at the catch (created at the pelvis). Both sweep and scull rowing showed values close to end range flexion for the lower lumbar spine at the catch and early drive phases. No difference (P > 0.05) was evident in lateral bend or axial rotation values for the lower lumbar region. Conclusions: Some differences exist in spinopelvic kinematics between sweep and scull ergometer rowing. However, it may be speculated that the lack of differences in lateral bend and axial rotation at the lower lumbar spine in sweep rowing may represent an adaptive and protective approach of experienced rowers. This may be the focus of future research studies.